Influence of coenzyme q10 on hyperlipidemia induced in mice - Hamed, Zena S; Al-Alsadoon, Labeeb H; Shaban, Khalid A; Taqa, Ghada A (Vojenské zdravotnické listy, 2022)
Background and objectives: hyperlipidemia is the hallmark of cardiovascular diseases, namely hypertension, ischemic heart diseases, and strokes. Treatment should be satisfactory to tackle the lipid disorder and maintain the circulatory normal lipid profile. Many factors/cofactors coordinate to maintain lipid levels within normal to avoid subsequent hazards associated with hyperlipidemia. Coenzyme Q10 is a ubiquitous endogenous biomolecule that plays an important biological role in the lipid catabolic pathway. The goal of the study is to define the role of Coenzyme Q10 in hyperlipidemic mice model induced manually.Methods: to do so, a diet based hyperlipidemia state was induced in mice and they were distributed into different groups to conform with our study objectives. A Coenzyme Q10 treated group was compared to the negative control group and the positive control group was used as well.Results: The biochemical and histological outcomes declared that Coenzyme Q10 has important lipid-reducing effects which are parallel or even superior to lipid reducing drugs (e.g. Rosuvastatin). Conclusion of the present study addressed the lipid-lowering properties of Coenzyme Q10 in a newly induced hyperlipidemia mouse model bestowing the use of Coenzyme Q10 as add-on adjuvant therapy in a high-risk group or as a monotherapy in a prophylactic group.
Keywords: rosuvastatin kalcium; Animals; Ubiquinone; Oxidative Stress; ubichinon; hyperlipidemie; zvířata; Mice; Disease Models, Animal; modely nemocí na zvířatech; oxidační stres; Hyperlipidemias; Rosuvastatin Calcium; myši